Reducing acidity of tropical acid soil to improve phosphorus availability and Zea mays L. productivity through efficient use of chicken litter biochar and triple superphosphate - Maru, Ali; Ahmed, Osumanu Haruna; Asap, Audrey; Nik Ab. Majid, Nik Muhamad; Maikol, Nathaniel; Jeffary, Alicia Vanessa (MDPI, 2020)
Phosphorus is a macronutrient which plays an important role in plant metabolism, growth, and development. However, in tropical acid soils, P fixation is high because of significant amounts of Al and Fe ions. Al and Fe ions can reduce diffusion of P into plant roots. Low absorption of P at initial growth of most plants causes stunting and slow growth of plant leaves. This process reduces photosynthesis. Chicken litter biochar (CLB) had been used on tropical acid soils to improve total P, available P, organic P, and inorganic fractions of P. Moreover, CLB is able to reduce exchangeable acidity, Fe, and Al ions in mineral acid soils because of the reactive surfaces of this organic amendment. However, there is dearth of information on the effects of the right combination of CLB and triple superphosphate (TSP) on the aforementioned soil chemical properties and crop productivity. To this end, the objectives of this study were to improve P: (i) Availability in a mineral acid soil and (ii) uptake, agronomic efficiency, and dry matter yield of Zea mays L. using the right amounts of TSP and CLB. Combinations of 75%, 50%, and 25% CLB (based on recommended 5 t ha−1) and TSP (based on recommended P fertilization for maize) were evaluated in a pot study. Selected soil chemical properties, maize plants nutrient uptake, growth variables, and dry matter yield were determined using standard measures. Results showed that 25% and 50% biochar of 5 t ha−1 with 75% TSP can increase soil P availability, recovery, agronomic use efficiency, and dry matter yield of maize plants. These optimum rates can also reduce P fixation by Al and Fe ions. Therefore, soil and maize productivity can be improved by using CLB (25% and 50% of 5 t ha−1) and TSP (75% of conventional rate) to increase nutrients availability especially P.